Study Of The Anti-Obesity Potential Of Chlorogenic Acid Through Molecular Docking - Faridah Faridah; Esti Mumpuni; Hari Purnomo; Dian Ratih Laksmitawati; Partomuan Simanjuntak (Journal of Social Research, 2024)
Chlorogenic acid, the primary constituent found in green coffee, is believed to possess anti-obesity properties. Numerous studies have indicated that the etiology of obesity is predominantly influenced by genetic factors. This study employs molecular docking techniques to estimate the effectiveness and toxicity of chlorogenic acid as an anti-obesity agent, focusing on its interaction with PLANTS. Initially, the validation process involved confirming the target cell or receptor (PDB code) which included PPAR-? (3NOA, 2ATH), pancreatic lipase (5ZUN), ghrelin (6ZYF), leptin (3V6O), and melanocortin (6W25, 7F58) through the utilization of YASARA software. In addition, the process of docking chlorogenic acid compounds and a positive control (for comparative purposes) was conducted on target cells utilizing the PLANTS program. The toxicity test and prediction of lethal dose (LD 50) were conducted on active substances and positive controls using the ProTox-II program. Chlorogenic acid exhibits anti-obesity properties by acting as an inhibitor of the ghrelin hormone, as seen by its activity at PDB code 6ZYF with a docking score of -19.7099 higher than the positive controls bupropion -18.5269 and naltrexone -18.5871. Furthermore, it has been determined to possess a generally safe profile, with an LD50 value of 5000 mg/kg body weight. The docking studies indicate that chlorogenic acid exhibits anti-obesity activity specifically at PDB code 6ZYF, where it functions as an inhibitor of the ghrelin hormone. Chlorogenic acid typically exhibits modest efficacy as an anti-obesity agent, hence presenting potential avenues for enhancing its effectiveness by structural modifications